"INSTITUTIONAL TRAPS» OF ENTREPRENEURSHIP UNDER DIGITALIZATION - I. Penkova (Вестник Северо-Кавказского федерального университета, 2022)
The main issues of the article characterize the novelty of the results obtained. They are following. The author insists that institutions and institutional traps are formed under the influence of historical background and modern processes of intensive digitalization; the institutional environment is under the multifactorial inluence of digitalization, both direct and indirect, and it has a positive and negative impact from the intensive processes taking place in the online space. The quality and efficiency of the functioning of entrepreneurship institutions directly depends on the technological component and information and technical readiness for large-scale global digitalization.